The Prevalence and Distribution of Spina Bifida in a Single Major Referral Center in Malaysia - Sahmat, Adibah; Gunasekaran, Renuka; Mohd-Zin, Siti W.; Balachandran, Lohis; Thong, Meow-Keong; Engkasan, Julia P.; Ganesan, Dharmendra; Omar, Zaliha; Azizi, Abu Bakar; Ahmad-Annuar, Azlina; Abdul-Aziz, Noraishah M. (Frontiers in Pediatrics, 2017)
Background: The aim of this study is to review the medical history of patients with spina bifida, encompassing both aperta and occulta types born between the years 2003 until 2016, spanning a 13-year time period. We assessed each patient and maternal parent information, details of the defects and conditions associated with the primary defect. We also include information on patients’ ambulation and education level (where available). Methods: Data from the Department of Patient Information University of Malaya Medical Centre (UMMC), Malaysia was captured from spina bifida patients (ICD10: Q05 spina bifida). Data involved patients referred to UMMC between 2003 and 2016 and/or born in UMMC within that particular time frame. We filtered and extracted the information according to the data of clinical examination, medical review and social history provided in the medical records. Results: A total of 86 patient records with spina bifida were analysed. Spina bifida prevalence rate in this study ranged from 0.89 - 1.87 per 1000 live births depending on weightage. We note that ethnicity was a factor whereby the highest numbers of spina bifida were from Malays (n= 36, 41.86 %), followed by equal numbers of Chinese and Indians (n=24, 27.91%). The highest number of diagnoses reported was myelomeningocele type-spina bifida (n= 39, 45.35 %). The most common site of the spina bifida lesion was located at the lumbar region irrespective of aperta or occulta types (n= 23, 26.74 %). Data on other associated phenotypes of spina bifida such as hydrocephalus and encephalocele was also captured at 37.21% (n=32) and 1.16% (n=1) respectively. In terms of mobility, 32.84% (n=22/67) of patients between the ages 4 to 16 years old were found to be mobile. As many as 36.07% of patients ranging from 5 to 16 years of age (n=22/61) received formal education ranging from preschool to secondary school. Conclusions: The prevalence of spina bifida in UMMC is as according to international statistics which is in the range of 0.5 -10 per 1000 live births. Majority of the reported cases were males, Malays, full term babies, and of the myelomeningocele phenotype located at the lumbar region.